2004
DOI: 10.1021/jp0367124
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Barriers, Charges, and Spin Densities in Alkyl Aryl Sulfide Radical Cations:  A Density Functional Study

Abstract: The structures and the torsional potentials for the rotation around the aryl-SR bond of a series of neutral alkyl aryl sulfides and their corresponding radical cations were studied by applying density functional theory at the B3LYP/6-311G** level. In all radical cations the most stable conformer corresponds to the structure in which the S-alkyl group is in the planar conformation, with sulfur and alkyl atoms coplanar with the aromatic ring. The rotational energy barriers were relatively high, ranging from 12.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…1[BF 4 ] 2 ⋅ y Me 2 CO and the structurally characterized phase of 1[BF 4 ] 2 ⋅MeCN contain a mixture of perpendicular and parallel S t Bu conformations, while desolvation of 1[ClO 4 ] 2 ⋅0.5 Me 2 CO⋅0.2 H 2 O involves rotation of a S t Bu group from a parallel towards a perpendicular orientation. In contrast, other 4‐alkylsulfanyl‐bpp derivatives and their iron complexes consistently adopt the “parallel” substituent conformation, [28–31] implying conjugation of the S atom lone pairs with the bpp pyridyl π ‐system [62] . The conformational variability in L and [Fe L 2 ] 2+ reflects the greater steric bulk of the S t Bu substituent, which evidently contributes to the unusually complicated spin‐state and crystal phase behavior in this system.…”
Section: Resultsmentioning
confidence: 98%
“…1[BF 4 ] 2 ⋅ y Me 2 CO and the structurally characterized phase of 1[BF 4 ] 2 ⋅MeCN contain a mixture of perpendicular and parallel S t Bu conformations, while desolvation of 1[ClO 4 ] 2 ⋅0.5 Me 2 CO⋅0.2 H 2 O involves rotation of a S t Bu group from a parallel towards a perpendicular orientation. In contrast, other 4‐alkylsulfanyl‐bpp derivatives and their iron complexes consistently adopt the “parallel” substituent conformation, [28–31] implying conjugation of the S atom lone pairs with the bpp pyridyl π ‐system [62] . The conformational variability in L and [Fe L 2 ] 2+ reflects the greater steric bulk of the S t Bu substituent, which evidently contributes to the unusually complicated spin‐state and crystal phase behavior in this system.…”
Section: Resultsmentioning
confidence: 98%
“…Another reaction that generates a positively charged functional group is the ionization of substituted methyl phenyl sulfoxides (Reaction 8 of Scheme 1), originally studied experimentally and computationally for a series of substituted examples by Baciocchi and Gerini. [48] In this case, we considered both the vertical ionization potential, that is, taking the radical cation geometry to be the same as that optimized for the neutral precursor, and also the adiabatic potential taking geometric relaxation of the radical cation into account. In the case of the nucleomers, the vertical IP then corresponds to using the neutral, unsubstituted geometry for nucleomer calculations, and the adiabatic IP is computed using the relaxed geometry of methyl phenyl sulfoxide radical cation (but not further relaxing when changing the nuclear charge).…”
Section: Resultsmentioning
confidence: 99%
“…A significant variation of the C–S bond cleavage rates was observed by changing the arylsulfenyl ring substituent . In this context, it has to be noted that previous theoretical studies carried out with a series of aryl-substituted thioanisole radical cations (in 4-X-C 6 H 4 -SCH 3 +• , X = H, CN, OMe, or N(CH 3 ) 2 ) showed remarkable differences in the charge and spin distribution on the aromatic ring depending on the nature of the substituent …”
Section: Introductionmentioning
confidence: 95%
“…13 In this context, it has to be noted that previous theoretical studies carried out with a series of aryl-substituted thioanisole radical cations (in 4-X-C 6 H 4 -SCH 3 +• , X = H, CN, OMe, or N(CH 3 ) 2 ) showed remarkable differences in the charge and spin distribution on the aromatic ring depending on the nature of the substituent. 14 Along this line, we considered it worthwhile to extend the analysis of the structural effects on the C−S bond cleavage in radical cations of aromatic sulfoxides by changing the substituents in the arylsulfinyl ring, taking into account that also in this case previous theoretical studies performed on aryl methyl sulfoxide radical cations 5 reported a remarkable effect of the aryl substituent on the charge and spin delocalization. In particular, it was found that in all the radical cations most of the charge and spin density are localized on the SOMe group, but a substantial delocalization was also observed on the aromatic ring (almost 50% for the methoxy derivative and 30% for the other radical cations).…”
Section: ■ Introductionmentioning
confidence: 99%